1996
DOI: 10.1016/s0896-6273(00)80219-6
|View full text |Cite
|
Sign up to set email alerts
|

Response and Habituation of the Human Amygdala during Visual Processing of Facial Expression

Abstract: We measured amygdala activity in human volunteers during rapid visual presentations of fearful, happy, and neutral faces using functional magnetic resonance imaging (fMRI). The first experiment involved a fixed order of conditions both within and across runs, while the second one used a fully counterbalanced order in addition to a low level baseline of simple visual stimuli. In both experiments, the amygdala was preferentially activated in response to fearful versus neutral faces. In the counterbalanced experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

109
954
19
17

Year Published

2000
2000
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,577 publications
(1,099 citation statements)
references
References 55 publications
109
954
19
17
Order By: Relevance
“…Within corrugator, early responses to angry expressions decreased over repeated trials, reflecting habituation which is typical of reflexive responses. There may be a relationship with the fast habituation of amygdalar responses to emotional facial expressions (Breiter et al, 1996;Whalen et al, 1998), in particular because the amygdala are involved in relatively fast, automatic facial mimicry reactions (Wild et al, 2003). Interestingly, as seen in Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Within corrugator, early responses to angry expressions decreased over repeated trials, reflecting habituation which is typical of reflexive responses. There may be a relationship with the fast habituation of amygdalar responses to emotional facial expressions (Breiter et al, 1996;Whalen et al, 1998), in particular because the amygdala are involved in relatively fast, automatic facial mimicry reactions (Wild et al, 2003). Interestingly, as seen in Fig.…”
Section: Discussionmentioning
confidence: 95%
“…There are also data suggesting that they may also be mutually excitatory, or at least that the amygdala may excite rACC (Budhani et al, 2007;Nakic et al, 2006;Pezawas et al, 2005). Specifically, rACC is found active in affective stimuli processing (Breiter et al 1996;Dolan et al 1996;Elliott et al 2000;George et al 1993). It is therefore possible that some of the results that were suggested to indicate control over the amygdala's response actually represented excitatory activation from the amygdala.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting a role for amygdala in face processing and social judgment, early neuroimaging studies found amygdala activation in response to facial expressions of emotion, particularly fear, even when subjects were not instructed to judge emotion [6,198]. Indeed, amygdala is activated by subliminal presentations of facial expression stimuli [199].…”
Section: The Neural Substrates For Recognition Of Emotion Expressionsmentioning
confidence: 99%